A simulation approach of under-hood thermal management. (October 2016) - Wang, Guohua; Gao, Qing; Zhang, Tianshi; Wang, Yan
Highlights: The approach is realized in coupling 1D simulation and 3D simulation. The 1D program and the combination module are compiled in MATLAB. The real time coupling is established in this approach. The approach is used in the under-hood thermal management. The heat flow and the heat interaction can be computed at same time. Abstract: Among the integrated design and analysis of the vehicle, the integrated simulation of vehicle thermal management system (VTMS) is an important approach. By the approach, the simulation of the multiple thermodynamic systems such as engine cooling system can be realized. In VTMS, the numerical simulation is an important means which is used to discuss the relevance of the multiple thermodynamic systems and the structure change. So the simulation approach coupling 1D simulation and 3D simulation is proposed to realize the comprehensive analysis. The 1D simulation is mainly about the relevance of systems and thermodynamic system cycles. The 3D simulation is mainly about the structure change. The MATLAB routine is used to compile the 1D model program and the combination module. The CFD software is used to compute the 3D simulation model in the multiple thermodynamic systems models. The combination module has the functions that include the 3D model combination and 1D relevance. Because the engine cooling, air conditioning, turbo charged cooling, oil cooling and others are set in the under-hood. The under-hood thermal management is the core of the integrated vehicle thermal management. So in this paper, the integrated simulation approach is mainly based on the under-hood 3D model. Through the integrated approach, the heat interaction and the heat flow are simulated and analysis together. The examples are supplied to illustrate the comprehensive and systematic analysis ability by the heat flow characteristics and the thermal interactions between the different systems and the components.